Small cell variant of osteosarcoma of the patella: A rare case report with review of literature - Ahmad, Javed; Patel, Brij Mohan (Asian Journal of Medical Sciences, 2024)
Patella is an uncommon site for the occurrence of bone tumor. Benign tumors are more common as compared to malignant ones. Osteosarcoma of the patella is a very rare tumor with only a few cases reported in the literature. Here, we present a rare case of a small-cell variant of osteosarcoma of the patella. A 12-year-old boy presented to us with pain and swelling over his left knee for 6 months. On X-ray, expansion with osteosclerotic and osteolytic lesions was found in the patella and a suspected diagnosis of osteosarcoma was made. The patient was managed by excisional biopsy of the patella and V–Y plasty of the quadriceps tendon. Results of histopathological and immunohistochemistry analyses were consistent with osteosarcoma of small cell variant. The patient was referred to a higher center after the operation for radiotherapy and chemotherapy. On the final follow-up, after 1 year, the patient was found to have expired. Osteosarcoma of the patella is a rare condition. Further studies with a number of cases and longer duration of follow-up are warranted to obtain better insight that can aid in devising management protocol, prediction of survival, and functional outcome of different surgical interventions for these patients.